A new imaging technology to reduce the radiation dose during uterine fibroid embolization. (December 2018) - Thomaere, Eveline; Dehairs, Michiel; Laenen, Annouschka; Mehrsima, Abdoli; Timmerman, Dirk; Cornelissen, Sandra; Op de Beeck, Katya; Bosmans, Hilde; Maleux, Geert
Background: Uterine fibroid embolization (UFE) is a minimally invasive imaging-guided treatment using radiation exposure. Purpose: To compare the patients' radiation exposure during UFE before and after introduction of a new X-ray imaging platform. Material and Methods: Forty-one patients were enrolled in a prospective, comparative two-arm project before and after introduction of a new X-ray imaging platform with reduced dose settings, i.e. novel real-time image processing techniques (AlluraClarity). Demographic, pre-interventional imaging, and procedural data, including dose area product (DAP) and estimated organ dose on the ovaries and uterus, were recorded and angiographic quality of overall procedure was assessed. Results: There were no significant differences in demographic characteristics and preoperative fibroid and uterine volumes in the two groups. The new imaging platform led to a significant reduction in mean total DAP (102 vs. 438 Gy.cm 2 ; P < 0.001), mean fluoroscopy DAP (32 vs. 138 Gy.cm 2 ; P < 0.001), mean acquisition DAP (70 vs. 300 Gy.cm 2 ; P < 0.001), and acquisition DAP estimated organ dose in ovaries (42 vs. 118 mGy; P < 0.001) and uterus (40 vs. 118 mGy, P < 0.001), without impairment of the procedure and angiographic image quality. Conclusion: A substantial 77% reduction of DAP values and 64% and 66% reduction in organ dose on ovaries and uterus, respectively, was demonstrated with the new imaging platform, while maintaining optimal imaging quality and efficacy.